Penerapan Teknik Boundary Value Analysis untuk Pengujian Aplikasi Penjualan Menggunakan Metode Black Box Testing - Siti Rika Yulistina; Tika Nurmala; Raden Muhamad Agung Trisakti Supriawan; Sandi Hidayat Ikhsan Juni; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2020)
Sales application is a financial transaction application, if something goes wrong can be detrimental to the owner, buyer, and employee. Then it needs to be tested to ensure the quality of the resulting application. Testing is a verification process for assessing the quality of a software to see whether the software meets the expected process and direction or not. The process that is not optimal can cause inequality of data to be stored in a database. Applications that have been programmed in such a way must go through a process step to ensure the level of quality of the software itself. Examples of processes that can be said to be good if they have a chance of getting an unknown error. Of the several types of Black Box testing methods one of them is Boundary Value Analysis. The method tests the maximum and minimum number of digits to produce a valid value and is easy enough to test sales applications at PT Global Advindo. In the first stage carried out in this study is to identify the functionality to be processed, ensuring the maximum and minimum number of digits matches the specified order. The result of applying the method used is the quality of the software is in accordance with the function, and can be utilized properly by user.